2020
DOI: 10.1002/advs.201903592
|View full text |Cite
|
Sign up to set email alerts
|

CACCT: An Automated Tool of Detecting Complicated Cardiac Malformations in Mouse Models

Abstract: Congenital heart disease (CHD) is the major cause of morbidity/mortality in infancy and childhood. Using a mouse model to uncover the mechanism of CHD is essential to understand its pathogenesis. However, conventional 2D phenotyping methods cannot comprehensively exhibit and accurately distinguish various 3D cardiac malformations for the complicated structure of heart cavity. Here, a new automated tool based on microcomputed tomography (micro‐CT) image data sets known as computer‐assisted cardiac cavity tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Histology and immunohistochemistry were performed as described previously ( Chu et al, 2020 ). Briefly, mouse embryos were dissected in PBS and fixed in 4% PFA overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Histology and immunohistochemistry were performed as described previously ( Chu et al, 2020 ). Briefly, mouse embryos were dissected in PBS and fixed in 4% PFA overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Although there are previous reports of automated segmentation and classification of CHD in mice [12][13][14][15][16] , they have several limitations. First, segmentation and analysis algorithms, when publicly available, typically require coding skills to be used, and hence call for user-friendly alternatives 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Congenital heart disease (CHD) is the most common structural birth defect with an incidence rate of 6-12 per 1,000 newborns (1)(2)(3)(4), and its estimated prevalence is about 19-20 per 1,000 newborns when the bicuspid aortic valve is included (5,6). In China, a national study reported an overall CHD prevalence of 9 per 1,000 newborns (7), and it remains the leading noninfectious cause of death in infancy and childhood despite tremendous progress in surgical therapies (8). CHD imposes a substantial burden on survivors, families, and societies.…”
Section: Introductionmentioning
confidence: 99%